2016
DOI: 10.1016/j.bcmd.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pain in sickle mice using facial expressions and body measurements

Abstract: Pain is a hallmark feature of sickle cell disease (SCD). Subjects typically quantify pain by themselves, which can be biased by other factors leading to overtreatment or under-treatment. Reliable and accurate quantification of pain, in real time, might enable to provide appropriate levels of analgesic treatment. The mouse grimace scale (MGS), a standardized behavioral coding system with high accuracy and reliability has been used to quantify varied types of pain. We hypothesized that addition of the objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…2B). Consistent with the findings from other cold pain measurements from other investigators, 24,34 these observations demonstrated the existence of cold-induced hypersensitivity in BERK mice.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2B). Consistent with the findings from other cold pain measurements from other investigators, 24,34 these observations demonstrated the existence of cold-induced hypersensitivity in BERK mice.…”
Section: Resultssupporting
confidence: 91%
“…49 Another group observed changes in mouse facial expression, body length and back curvature in response to noxious cold (4 °C). 34 Together with the findings of the current study, it is clear that BERK mice exhibited hypersensitivity to both mild and extremely cold stimuli, which was also reported by patients with SCD. 2,12,35 …”
Section: Discussionsupporting
confidence: 88%
“…Patients with SCD had decreased pain thresholds for heat and cold stimuli [10]. Consistent with patient reports, hyperalgesia to cold and heat occurs in HbSS-BERK sickle mice [12,38,27,48,65]. In our study, C-fiber nociceptors sensitive to heat stimuli did not show lower thresholds but cumulative responses were higher than those in HbAA mice.…”
Section: Discussionsupporting
confidence: 89%
“…SCD mice also express deep tissue, non-stimulus evoked pain, and musculoskeletal pain measured by decreased grip force strength, decreased voluntary wheel running[22; 29], altered grimace, body length and stature scores associated with chronic pain[41], and anxiety and depression-like behaviors[29; 31] which correlate the comorbidities of depression and anxiety in SCD patients. [57; 60] Female and male mice exhibit similar magnitudes of hypersensitivity[23], consistent with both female and male patients enduring the severe pain.…”
Section: Sickle Mice Exhibit Prominent Chronic Evoked and Ongoing Pamentioning
confidence: 99%